Pengembangan Sumber dan Evaluasi Pembelajaran Sekolah Dasar Menggunakan Moodle Berbasis Virtual Machine - Soelistijanto, Bambang; Hernawan, Agung; Hadhiatma, Agung (Jurnal Atma Inovasia, 2024)
Information technology-based learning has become a significant method to enhance the quality of education. Information technology allows students to learn without being limited by time and space. Students can also study and practice independently according to their capacity and needs. E-learning is a learning methodology that requires information technology. One of the information technologies that has been used for learning is Moodle. Moodle is a learning management system" (LMS) used to organize, deliver learning materials, and assess students' competencies. Like a general web page, Moodle has features for presenting classes and courses, where teachers can upload teaching materials, questions, and assignments. Students can log into Moodle and select the classes provided or registered for them. Student activities in Moodle will be monitored for learning progress and evaluation grades. In Indonesia, Moodle has been used by secondary schools, universities, and companies for e-learning. This workshop on Learning Management Systems (LMS) especially for rural students is considered as their level of computer literacy still needs improvement.